Pharmacologic Treatment of Transplant Recipients Infected With SARS-CoV-2: Considerations Regarding Therapeutic Drug Monitoring and Drug–Drug Interactions. Issue 3 (June 2020) - Elens, Laure; Langman, Loralie J.; Hesselink, Dennis A.; Bergan, Stein; Moes, Dirk Jan A.R.; Molinaro, Mariadelfina; Venkataramanan, Raman; Lemaitre, Florian
Abstract : Background: COVID-19 is a novel infectious disease caused by the severe acute respiratory distress (SARS)-coronavirus-2 (SARS-CoV-2). Several therapeutic options are currently emerging but none with universal consensus or proven efficacy. Solid organ transplant recipients are perceived to be at increased risk of severe COVID-19 because of their immunosuppressed conditions due to chronic use of immunosuppressive drugs (ISDs). It is therefore likely that solid organ transplant recipients will be treated with these experimental antivirals. Methods: This article is not intended to provide a systematic literature review on investigational treatments tested against COVID-19; rather, the authors aim to provide recommendations for therapeutic drug monitoring of ISDs in transplant recipients infected with SARS-CoV-2 based on a review of existing data in the literature. Results: Management of drug–drug interactions between investigational anti-SARS-CoV-2 drugs and immunosuppressants is a complex task for the clinician. Adequate immunosuppression is necessary to prevent graft rejection while, if critically ill, the patient may benefit from pharmacotherapeutic interventions directed at limiting SARS-CoV-2 viral replication. Maintaining ISD concentrations within the desired therapeutic range requires a highly individualized approach that is complicated by the pandemic context and lack of hindsight. Conclusions: With this article, the authors inform the clinician about the potential interactions of experimental COVID-19 treatments with ISDs used in transplantation. Recommendations regarding therapeutic drug monitoring and dose adjustments in the context of COVID-19 are provided.